Postural stability and risk of falls per decade of adult life – a pilot study - Sieńko-Awierianów, Elżbieta; Lubkowska, Anna; Kolano, Piotr; Chudecka, Monika (Anthropological Review, 2018)
A gradual loss of function in the balance system may begin in the fourth decade of life. The effects of this process become visible in old age, when problems with postural stability contribute to falls, making it an important social problem. Early detection of this dysfunction is essential for minimizing the risk of age-related falls, one of the main causes of hospitalization or even death in older adults. The aim of this study was to evaluate somatic factors that may result in the deterioration in postural stability and determine the age range in which the first changes in stability occur. The study included healthy non-sporting adults aged from 20 to 70 years. Four tests based on the Biodex Balance System were used to determine static postural stability, dynamic postural stability, risk of falling and stability limits. The obtained results showed that dysfunctions of dynamic balance appeared significantly earlier than static balance dysfunctions, i.e. as early as at 50 years of age, and then gradually increased. Higher BMI and the percentage and absolute fat content significantly increased the risk of falls and also adversely affected the results of dynamic stability tests.